Use Of Ankle Immobilization In Evaluating Treatments To Promote Longitudinal Muscle Growth In Mice. Issue 5 (2nd October 2018) - Tinklenberg, Jennifer; Beatka, Margaret; Bain, James L. W.; Siebers, Emily M.; Meng, Hui; Pearsall, R. Scott; Lawlor, Michael W.; Riley, Danny A.
ABSTRACT: Introduction : Difficulty in modeling congenital contractures (deformities of muscle‐tendon unit development that include shortened muscles and lengthened tendons) has limited research of new treatments. Methods : Early immobilization of the ankle in prepuberal mice was used to produce deformities similar to congenital contractures. Stretch treatment, electrostimulation, and local intramuscular injection of a follistatin analog (FST‐288) were assessed as therapeutic interventions for these deformities. Results : Ankle immobilization at full plantarflexion and 90 ° created tendon lengthening and muscle shortening in the tibialis anterior and soleus. Stretch treatment produced minimal evidence for longitudinal muscle growth and electrostimulation provided no additional benefit. Stretch treatment with FST‐288 produced greater longitudinal muscle growth and less tendon lengthening, constituting the best treatment response. Discussion : Ankle immobilization recapitulates key morphologic features of congenital contracture, and these features can be mitigated by a combination of stretch and pharmacological approaches that may be useful in patients. Muscle Nerve 58 : 718–725, 2018